2007
DOI: 10.2337/db06-1662
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective and Anti-Inflammatory Effects of Interleukin Converting Enzyme Inhibition in Experimental Diabetic Cardiomyopathy

Abstract: OBJECTIVE-We investigated the effect of pharmacological inhibition of the interleukin converting enzyme (ICE) on cardiac inflammation, apoptosis, fibrosis, and left ventricular function in an animal model of diabetes.RESEARCH DESIGN AND METHODS-Diabetes was induced in 24 Sprague-Dawley rats by injection of streptozotozin (STZ) (70 mg/kg). Diabetic animals were treated with the interleukin converting enzyme (ICE) inhibitor (ICEI) (n ϭ 12) or with a placebo (n ϭ 12). Nondiabetic rats served as controls (n ϭ 12).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
94
3

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 124 publications
(104 citation statements)
references
References 42 publications
(42 reference statements)
7
94
3
Order By: Relevance
“…In agreement with the direct anti-inflammatory properties of HDL (Cockerill et al 2001;Hyka et al 2001), apo A-I transfer decreased the diabetes-induced intramyocardial inflammation (Westermann et al 2007b, c) as indicated by the reduction in ICAM-1, vascular cell adhesion molecule (VCAM)-1, and TNF-α mRNA expression ) and VCAM-1 protein expression (Van Linthout et al 2010b). Downregulation of VCAM-1/ICAM-1 expression suppresses monocyte-endothelial cell adhesion and subsequent transendothelial migration of inflammatory cells.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-induced Cardiacmentioning
confidence: 59%
“…In agreement with the direct anti-inflammatory properties of HDL (Cockerill et al 2001;Hyka et al 2001), apo A-I transfer decreased the diabetes-induced intramyocardial inflammation (Westermann et al 2007b, c) as indicated by the reduction in ICAM-1, vascular cell adhesion molecule (VCAM)-1, and TNF-α mRNA expression ) and VCAM-1 protein expression (Van Linthout et al 2010b). Downregulation of VCAM-1/ICAM-1 expression suppresses monocyte-endothelial cell adhesion and subsequent transendothelial migration of inflammatory cells.…”
Section: Human Apo A-i Gene Transfer Reduces Diabetes-induced Cardiacmentioning
confidence: 59%
“…Recently, it was shown that immunocompetent cells like T-cells (CD3 ϩ ) can indeed alter tissue remodelling in vitro, 45 and we have shown that cardiac inflammation is associated with excessive collagen accumulation in experimental diabetic cardiomyopathy in 1 animal model of HFNEF. 25 There is experimental and clinical evidence that inflammatory cells might modulate cardiac function in HF with reduced 46,47 and normal 48,49 EF. The direct effects of these cells are still under debate, but it has been suggested that increased inflammation is associated with the development of systolic HF by distinct changes in the ratio of MMP to TIMP.…”
Section: Discussionmentioning
confidence: 99%
“…[122][123][124][125] Cardiac inflammation and leukocyte recruitment, as observed in the setting of diabetic cardiomyopathy, seems to be mediated in part through the NLRP3 inflammasome in a similar fashion to MI. 68,[126][127][128][129][130] It has been hypothesized that the mechanism of inflammasome activation in diabetic cardiomyopathy is dependent on the combination of oxidative stress and reactive oxygen species production, as a result of mitochondrial dysfunction. 131,132 Damaged mitochondria are removed from the cell in a process known as mitophagy, and if this system is overwhelmed or ineffective, increased reactive oxygen species ensues.…”
Section: Diabetic Cardiomyopathy and Chronic Inflammationmentioning
confidence: 99%